PERAN MEDIA TEKNOLOGI DAN INFORMASI TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS TINGGI SEKOLAH DASAR - Suci Handayani; Munawir Gazali, Meri Yuliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine how well the use of information technology-based learning media on the learning interests of fifth grade students of SDN Mertak Tombok. The population and sample in this study were 25 students. The data analysis technique used was descriptive statistics. The results of the data analysis showed that the value of the Social Studies Subject of the Upper Elementary School Class was 76.94% of the expected value.